Diagnostic Comparison of Different Methods for Detection of Occlusal Caries Lesions in New Erupted Permanent Teeth - İpek, İrem; Öznurhan, Fatih; Derdiyok, Cansu; Keskuş Şengül, Büsra (Ataturk Universitesi, 2025)
Objective: The aim of this study is to evaluate the effectiveness of the alternating current impedance spectroscopy device in the diagnosis of occlusal caries using visual and radiovisiography and determining the inter-researcher reliability of the device by repeating it with two different researchers. Materials and Methods: From thirty-five patients, a total of thirty-five new eruptive occlusal first molar teeth with intact or early decay were included. It was examined by visual, radiovisiography and CarieScan Pro (CP) device by two researchers with independent clinical experience. Results: With regard to intra-observer agreement for examiner 1 and 2, while there was only statistically significant difference between CP and ICDAS-II (P<.005), no significant difference was found among other groups. A high inter observer agreement and moderately good kappa value were seen. Conclusion: The ICDAS-II method alone appears to be sufficient for the diagnosis of occlusal caries. It was concluded that the CP technique showed a low ability to reveal occlusal carious lesions on enamel and/or dentin in newly erupted permanent molars. © 2025, Ataturk Universitesi. All rights reserved.
Yeni Sürmüş Daimi Dişlerde Oklüzal Çürük Lezyonlarının Tespiti İçin Farklı Yöntemlerin Tanısal Karşılaştırması
Keywords: Caries Diagnosis; CarieScan Pro; ICDAS-II